The efficiency of high-flow nasal cannula for adult patients with coronavirus disease 19 in Jeddah, Saudi Arabia - Majid S Al-Thaqafy; Saleh Alzahrani; Abdulwahab Alghamdi; Saleh Alselemi; Khalid Alshebani; Bussma Ahmed Bugis; Alaa Bugis; Ali S Al-Shareef (Annals of Thoracic Medicine, 2022)
CONTEXT: Early use of a high-flow nasal cannula (HFNC) provides positive outcomes for preventing the risk of intubation. However, the efficiency and usage of HFNC in the case of coronavirus disease 2019 (COVID-19) among adult patients with multiple risk factors remain debatable and require more investigation. AIMS: The aim of this study was to determine the efficiency of HFNC in preventing the possible risk of intubation. SETTINGS AND DESIGN: This study was an observational cross-sectional study that was conducted at a selected hospital in Jeddah, Saudi Arabia, from July 2020 to August 2021. METHODS: The data were collected from patients' medical records through the hospital health information system. Adult COVID-19 patients who used HFNC were included, while those who used bilevel positive airway pressure or continuous positive airway pressure without any trials of HFNC and neonatal or pediatric patients were excluded. The exposure of HFNC setting which included variables such as percentages of the fraction of inspired oxygen and the duration of using HFNC were measured to find the relation with respiratory rate oxygenation (ROX) index as a measurement of patient outcome. STATISTICAL ANALYSIS USED: The data were analyzed by using the online calculator socscistatistics.com for prevalence statistics, and correlation tests of significance. Prevalence statistics were presented in mean, median, frequencies, and percentages. Statistical tests were used to measure correlations of key variables. P < 0.05 of ANOVA and t-tests was considered statistically significant. RESULTS: A total of 159 adult COVID-19 patients using HFNC were included, and most of these patients were male. The median age was 64 years. Most of patients were reported to have hypertension and diabetes mellitus. The majority (94.34%) of patients were successfully weaned from HFNC and shows effective intervention with a mean of 7.53 of ROX score. Appropriate implementation of HFNC might be a successful intervention for preventing the risk of intubation. CONCLUSIONS: According to the success rate of HFNC, which was considered a positive outcome, there might be a promising intervention for HFNC to prevent the risk of intubation and decrease the mortality rate.